2017
DOI: 10.1080/10717544.2016.1245366
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oral bioavailability and anticancer efficacy of fisetin by encapsulating as inclusion complex with HPβCD in polymeric nanoparticles

Abstract: Fisetin (FST), a potent anticancer phytoconstituent, exhibits poor aqueous solubility and hence poor bioavailability. The aim of the present study is to improve the oral bioavailability of FST by encapsulating into PLGA NPs (poly-lactide-co-glycolic acid nanoparticles) as a complex of HPbCD (hydroxyl propyl beta cyclodextrin) and to assess its anti-cancer activity against breast cancer cells. FST-HPbCD inclusion complex (FHIC) was prepared and the supramolecular complex formation was characterized by FTIR, DSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 35 publications
(39 reference statements)
1
41
0
Order By: Relevance
“…Recent studies reported the use of microencapsulation for preparing fisetin formulations (Kadari et al . ). However, few studies report the use of S. cerevisiae cells for this purpose.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies reported the use of microencapsulation for preparing fisetin formulations (Kadari et al . ). However, few studies report the use of S. cerevisiae cells for this purpose.…”
Section: Resultsmentioning
confidence: 97%
“…As previously commented, the addition of a third osmoporation stage under the conditions used in the present study adds, on average, 2 h and 30 min to the process, which may not be of interest as the gains are low. Recent studies reported the use of microencapsulation for preparing fisetin formulations (Kadari et al 2017). However, few studies report the use of S. cerevisiae cells for this purpose.…”
Section: Increase Of Fisetin Osmoporation Into S Cerevisiae Cellsmentioning
confidence: 99%
“…The low solubility and low bioavailability of fisetin limit its further investigation. Previous studies have attempted to overcome these issues with the use of drug delivery vectors and improved preparation techniques ( 35 , 52 ), and it is expected that future studies will provide strategies for further clinical and translational research on fisetin.…”
Section: Discussionmentioning
confidence: 99%
“…Fisetin, a dietary flavonol, is known to improve glucose homeostasis and mitigates diabetic complications [43]. Several nanoformulations, such as fisetin-PLGA-hyroxypropyl β-cyclodextrin nanoparticles, fisetin-assembled solid lipid nanoparticles, and fisetin-loaded nanoemulsion, were reported to improve oral bioavailability and gastrointestinal stability of fisetin [165,315,316]. Fisetin-PCL-PLGA-PEG-COOH nanoparticles have been claimed to be an attractive formulation with an improved pharmacokinetic profile for efficient management of hyperglycaemia and oxidative stress [317].…”
Section: Other Plant-derived Antidiabetic Nanoformulationsmentioning
confidence: 99%